FRI0159 REAL-WORLD EVIDENCE OF EFFECTIVENESS OF SWITCHING FROM TOFACITINIB 5MG BID TO TOFACITINIB 11MG QD IN A COHORT OF PATIENTS WITH RHEUMATOID ARTHRITIS: A SINGLE-CENTER, OBSERVATIONAL STUDY IN TAIWAN. (June 2019) - Lin, Liang-Hung; Chen, Der-Yuan
Abstract : Background: Rheumatoid arthritis (RA) is a chronic autoimmune disorder, precipitating chronic inflammation of the joints, also affecting organs throughout the body. For chronic conditions, such as RA, a once-daily (QD) dosing option has the potential to optimize patient adherence, and may enhance patient convenience and ease of use. Real-world data on effectiveness of switching from tofacitinib 5mg BID to 11mg QD is scarce. Objectives: This study aimed at evaluating the effectiveness and safety of RA patients switching from tofacitinib 5mg BID to tofacitinib 11mg QD in a real-world setting. Methods: A retrospective chart review of patients with RA was performed at the rheumatology department of an integrated secondary teaching hospital in Taiwan. The following cohorts were defined: RA patients who switched from tofacitinib 5mg BID to tofacitnib 11mg QD between 1 July 2018 and October 2018, and the follow-up period was at least 3 months. The clinical demographics and laboratory variables were obtained from clinic records. Results: As of December 2018, 71 patients were included (85% of women), with a mean (SD) age of 57.4 (12.7) years, 70.1% were biologic-experienced; 78.9% rheumatoid factor positive and 80.3% anti- citrullinated peptide antibody (ACPA) positive. At baseline (before patients initiated tofacitnib 5mg BID treatment), the mean DAS28-ESR was 5.0 (8.4% patients with low disease activity, and 2.8% in clinical remission), the mean CDAI was 23.0 (11.2% patients with low disease activity, and 0% in clinical remission). After an average duration of 20 months treatment on tofacitinib 5mg BID treatment, the mean DAS28-ESR was 3.3 (29.6% patients with low disease activity, and 2.8% in clinical remission), the mean CDAI was 7.5 (84.5% patients with low disease activity, and 2.8% in clinical remission). While switching to tofacitnib 11mg QD for 3 months, no significant difference was observed in terms of the ratio of DAS28-ESR LDA or CDAI LDA, but numerically more patients achieved DAS28-ESR LDA or CDAI LDA (32 and 64, respectively). During the 3-month follow-up period, no new adverse events were present. Conclusion: Our study showed that RA patients switching from tofacitnib 5mg BID to tofacitnib 11mg QD sustained the effectiveness with no adverse clinical impact. References: [1] Lamba M, Wang R, Fletcher T, et al. J Clin Pharmacol. 2016 Nov;56(11):1362-1371 [2] Kuo CF, Luo SF, See LC, et al. Rheumatol Int. 2013 Feb;33(2):355-60. Disclosure of Interests: None declared